Evaluation of FeMnN alloy bioresorbable flow diverting stents in the rabbit abdominal aorta - Alexander A. Oliver; Cem Bilgin; Mitchell L. Connon; Andrew J. Vercnocke; Esref A. Bayraktar; Jonathan Cortese; Daying Dai; Yong Hong Ding; Sarah A. Erdahl; John Pederson; Kent D. Carlson; Adam J. Griebel; et al. (Bioactive Materials)
Flow diverting stents are braided, metallic endoluminal devices widely used to treat intracranial aneurysms. Bioresorbable flow diverters (BRFDs) are gaining traction as the next generation of flow diverter technology. BRFDs aim to occlude and heal the aneurysm before safely dissolving into the body, mitigating or eliminating complications associated with the permanent presence of conventional flow diverters such as thromboembolism and stenosis. Additional putative advantages of a BRFD include a reduction in metal induced medical imaging artifacts, a restoration of physiological vasoreactivity, and allowing physicians to re-access the aneurysm if an additional procedure is required. In this current study, iron-manganese-nitrogen (FeMnN) alloy BRFDs and permanent control FDs composed of an industry standard Cobalt-Nickel-Chromium alloy were deployed in the rabbit aorta. MicroCT and SEM corrosion analysis determined the FeMnN wire volumes and cross-sectional areas had reduced approximately 85 % and 95 % after 3- and 6-months implantation duration, respectively. Histological analysis demonstrated the BRFDs exhibited suitable biocompatibility, with no cases of in-stent thrombosis, clinically significant stenosis, or adverse tissue responses observed. Immunohistochemistry revealed the neointimas surrounding the BRFDs featured a confluent endothelium covering several layers of smooth muscle cells, with macrophages adjacent to the device wires. The macrophages were able to penetrate the corrosion product and were observed transporting corrosion products away from the implant site. This current work provides primary in vivo corrosion and biocompatibility data to the field for FeMn alloys, which we feel will stimulate and inform the design of next-generation bioresorbable endovascular devices.